PENGEMBANGAN PROTOTIPE ALAT BANTU LATIHAN MENGAYUN PADA CABANG OLAHRAGA WOODBALL DI JAWA TENGAH - Anas Kholikul Amin; Muchsin Doewes; Sapta Kunta Purnama (Universitas Muhammadiyah Semarang, 2017)
The purpose of the research was to develop a model tools swing that can be used to swing training for men's athlete woodball beginner and advanced level with the aim to improve the skills of swing movement. This equipment can be used for practicing male woodball on beginner advanced men's level. This study used a qualitative approach for model development. The data collected in this study either at initial as well as trial stages were qualitative data. The main procedure in the research and development consists of five steps, namely: (1) analyze product to be developed; (2) develop early product; (3) Validation by the expert; (4) The field trials; (5) Revision of product. The results of this study concluded that the development model of swing training can be used to (1) improve the skills of swing motion for men's athlete woodball beginner and advanced level; (2) As a means of training for men's athlete woodball beginner and advanced level. Keywords: Development, swing trainer, woodball